Socialization and Simple Bookkeeping Practice in Joint Business Dasa Wisma Rosella, Lempake Village - Farras Aprilia Arghyanti; Sri Ngapiyatun; Shera Vanessa Sarazar; Miranti Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Dasa Wisma Rosella is one of the business groups in RT 19, Lempake Village, North Samarinda District. This joint venture group produces various products made from rosella flowers, including syrup and jam. The production activities of the Dasa Wisma business group still use simple financial management, there is no neatly organized bookkeeping system so that there are no financial statements produced every month that can be used as material for business evaluation and supervision due to limited knowledge of members about financial statements so that the results of the business are not too visible, because without good financial management a business group will find it difficult to understand the conditions his own efforts well. This community service activity aims to educate and provide direct counseling on the importance of good and correct bookkeeping in financial recording techniques or proper business bookkeeping to Dasa Wisma Rosella 1 business actors. The method used is observation and direct practice to the field. The results of these community service activities are 1) increased knowledge about the importance of recording Dasa Wisma Rosella's business financial transactions, 2) increased knowledge about forms of financial recording tools such as bookkeeping, income statements including by calculating the cost of goods produced from the products they produce. The benefit of this community service activity is that the community can know how to do good and correct bookkeeping with simple accounting. After conducting counseling with direct practice, now the members of Dasa Wisma can understand and understand how to record financial transactions into accounting bookkeeping simply.Dasa Wisma Rosella dapat dikatakan sebagai bagian dari kelompok usaha yang ada di RT 19 Kelurahan Lempake Kecamatan Samarinda Utara. Kelompok usaha bersama ini memproduksi berbagai produk yang berbahan dasar bunga rosella, antara lain ada sirup dan selai. Kegiatan produksi kelompok usaha Dasa Wisma ini masih menggunakan pengelolaan keuangan secara Belum ada sistem pembukuan yang terorganisir dengan baik, sehingga belum tersedia laporan keuangan bulanan yang bisa digunakan untuk evaluasi dan pengambilan keputusan. Pengawasan usaha karena keterbatasan pengetahuan anggota tentang laporan keuangan sehingga hasil dari usaha tersebut tidak terlalu tampak, karena tanpa adanya pengelolaan keuangan yang baik suatu kelompok usaha akan sulit memahami kondisi usahanya sendiri dengan baik. Kegiatan pengabdian pada Program pengabdian ini bertujuan untuk memberikan edukasi dan penyuluhan langsung tentang pentingnya pencatatan keuangan yang tepat kepada pelaku usaha di Dasa Wisma Rosella 1. Metode yang digunakan meliputi observasi dan praktik lapangan. Hasil dari kegiatan ini meliputi: 1) peningkatan pengetahuan mengenai pentingnya pencatatan transaksi keuangan usaha Dasa Wisma Rosella, 2) peningkatan pemahaman tentang berbagai alat pencatatan keuangan seperti pembukuan, laporan laba rugi, serta cara menghitung harga pokok produksi dari produk yang dihasilkan. Manfaat dari kegiatan ini adalah para anggota Dasa Wisma kini dapat memahami dan menerapkan pembukuan sederhana dengan menggunakan konsep akuntansi dasar setelah mengikuti penyuluhan dan praktik langsung.